Laser cladding Al / FeCrAl gradient coating used for garbage incineration working condition and preparation method of laser cladding Al / FeCrAl gradient coating
By using laser cladding technology to prepare Al/FeCrAl gradient coating in high-temperature corrosion environments such as waste incineration power generation, the limitations of the existing FeCrAl coating in extreme corrosion environments are solved, and efficient and economical corrosion resistance and high temperature are achieved. stability.
Patent Information
- Application Number
- CN202411674104.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
In high-temperature corrosion environments such as waste incineration power generation, there are limitations in the application of existing FeCrAl coatings in extreme corrosion environments containing chlorides and sulfates. How to improve its density and bonding strength to enhance corrosion resistance has become a challenge.
The Al/FeCrAl gradient coating is prepared on the surface of the matrix material by laser cladding technology. By forming a FeCrAl alloy hybrid coating on the surface of the aluminum alloy coating, combined with the precise control of the laser cladding process, we ensure the good combination of the coating and the matrix material.
It achieves excellent corrosion resistance in high-temperature sulfate and chloride corrosion environments, improves the high-temperature stability and durability of the coating, and reduces production costs, achieving cost-effectiveness and efficiency comparable to nickel-based alloy performance.
Smart Images

Figure CN119506865A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface coating preparation, and particularly relates to a laser cladding Al / FeCrAl gradient coating for waste incineration conditions and a preparation method thereof. Background Art
[0002] As global energy and environmental issues become increasingly prominent, high-temperature corrosive environments such as waste incineration power generation have put forward higher requirements on the long-term service performance of equipment materials. In such extreme environments, a large amount of chlorides and sulfates (such as KCl, Na2SO4) produced by fuel combustion pose a great corrosion threat to metal materials, leading to rapid failure of materials. Although traditional heat-resistant steels have certain corrosion resistance, their durability is insufficient under the harsh effects of corrosive media such as sulfates and chlorides. Nickel-based alloys exhibit excellent corrosion resistance at high temperatures, but their high cost limits their large-scale industrial applications. Therefore, it is urgent to develop a coating material that has both excellent corrosion resistance and economical and efficient performance.
[0003] As an efficient surface modification method, laser cladding technology uses a high-energy laser beam to quickly melt the coating material and achieve good metallurgical bonding with the substrate, significantly improving the surface performance without affecting the substrate properties. In particular, FeCrAl coatings, with their excellent oxidation resistance and high-temperature corrosion resistance, have become ideal protective coatings in harsh environments such as waste incineration power generation. Although FeCrAl coatings exhibit good oxidation resistance, their application in extreme corrosive environments containing chlorides and sulfates still has certain limitations. Therefore, how to improve the density and bonding strength of the coating by optimizing the process, and thus improve its corrosion resistance, is the main challenge of current research. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a laser cladding Al / FeCrAl gradient coating for waste incineration conditions, aiming to solve the technical problem that the existing nickel-based alloy has excellent high-temperature corrosion resistance but high cost. The present invention also provides a preparation method of the laser cladding Al / FeCrAl gradient coating.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A laser cladding Al / FeCrAl gradient coating for waste incineration conditions comprises an aluminum alloy coating arranged on the surface of a base material and a FeCrAl alloy mixed coating arranged on the surface of the aluminum alloy coating.
[0007] In some specific embodiments, the thickness of the laser cladding Al / FeCrAl gradient coating is 0.5-1.2 mm.
[0008] In some specific embodiments, the particle size of the aluminum alloy powder in the aluminum alloy coating is 15-53 μm, the particle size of the Fe, Cr, and Al metal powders in the mixed coating is 15-53 μm, and the mixed coating, by mass percentage, includes Fe: 75-85%, Cr: 10-15%, and Al: 4-10%.
[0009] A method for preparing the aforementioned laser cladding Al / FeCrAl gradient coating comprises the following steps:
[0010] 1) Pre-treat the substrate material by sandblasting to remove oxides, and clean it with anhydrous ethanol and then dry it;
[0011] 2) Using laser cladding process to prepare aluminum alloy coating on the surface of substrate material;
[0012] 3) In terms of mass percentage, metal powders of Fe: 75-85%, Cr: 10-15%, and Al: 4-10% are mixed, and a uniform powder is obtained by vacuum ball milling. Subsequently, a FeCrAl alloy mixed coating is prepared on the surface of the aluminum alloy coating by a laser cladding process.
[0013] Furthermore, before step 1), the surface of the base material is subjected to sandblasting or mechanical grinding to remove oxides.
[0014] In some specific embodiments, in step 2), the processing parameters of the laser cladding are: laser power of 1000-1500 W, scanning speed of 50-66 mm / s, powder feeding speed of 6-12 g / min, and spot diameter of 3 mm.
[0015] Furthermore, in step 2), the processing parameters of the laser cladding are: laser power is 1250 W, scanning speed is 55 mm / s, powder feeding speed is 9 g / min, and spot diameter is 3 mm.
[0016] In some specific embodiments, in step 3), the processing parameters of the laser cladding are: laser power 1500-2500 W, scanning speed 11-44 mm / s, powder feeding speed 9-15 g / min, and spot diameter 3 mm.
[0017] Furthermore, in step 3), the processing parameters of the laser cladding are: laser power 2250 W, scanning speed 22 mm / s, powder feeding speed 12 g / min, and spot diameter 3 mm.
[0018] In some specific embodiments, argon gas protection is used, the carrier gas flow rate is 15-20 L / min, and the protective gas flow rate is 10-15 L / min.
[0019] In certain specific embodiments, in step 3), the ball milling conditions are as follows: a rotation speed of 100-200 r / min, a ball-to-material ratio of 8:1-12:1, and a ball milling time of 2-6 h.
[0020] In some specific embodiments, the aluminum alloy powder, and the Fe, Cr, and Al metal powders all have a particle size of 15-53 μm.
[0021] The aforementioned laser cladding Al / FeCrAl gradient coating is suitable for high-temperature sulfate and chloride corrosion in the waste incineration power generation environment.
[0022] Compared with the prior art, the present invention has at least the following advantages:
[0023] 1) The Al / FeCrAl gradient coating provided by the present invention is a dense Al / FeCrAl composite structure, and / or forms a dense Al2O3 protective film on the surface of the Al / FeCrAl gradient coating, which effectively prevents the penetration of corrosive media; the Al / FeCrAl gradient coating not only enhances the overall corrosion resistance of the coating, but also improves the high temperature stability and durability of the coating; at the same time, due to the use of aluminum alloy powder as the material, the cost of aluminum alloy materials is significantly reduced compared with traditional nickel-based alloys. This not only reduces production costs, but also improves the economy of engineering applications, and under the same laser cladding process parameters, the Al / FeCrAl gradient coating is comparable to nickel-based alloys (such as Inconel 625) in performance, especially in high temperature corrosion environments. Excellent corrosion resistance, thereby maintaining the performance of nickel-based alloys while achieving cost control.
[0024] 2) The preparation method of the Al / FeCrAl gradient coating provided by the present invention ensures good bonding between the coating and the base material by laser cladding technology and precisely controls the processing parameters of the laser cladding, thereby reducing the generation of defects such as cracks and voids. The process improves the adhesion and bonding strength of the coating, realizes the preparation of a dense Al / FeCrAl gradient coating on the surface of the base material, and / or promotes the formation of a dense Al2O3 protective film, effectively preventing the penetration of corrosive media; it is particularly suitable for superheater pipes in waste incineration power generation environments.
[0025] 3) The preparation method of the Al / FeCrAl gradient coating provided by the present invention achieves uniform coating coverage and thickness controllability through layer-by-layer deposition and precise process control, and has high process repeatability and production efficiency. In addition, the use of laser cladding technology can perform local surface treatment, reduce material waste and processing time, and further reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0027] Figure 1 This is a microstructure photograph of the cross-section morphology of the Al / FeCrAl gradient coating in Example 2;
[0028] Figure 2 This is a cross-sectional microstructure photograph of the Al / FeCrAl gradient coating in Example 3;
[0029] Figure 3 XRD comparison diagram of the composite coating in Example 2-3 and Comparative Example 2-3;
[0030] Figure 4 This is a macroscopic photograph of the cross-sectional morphology of the composite coating sample in Comparative Example 1;
[0031] Figure 5 This is a cross-sectional microstructure photograph of the Al / FeCrAl gradient coating in Comparative Example 2;
[0032] Figure 6 The cross-sectional microstructure photograph of the Al / FeCrAl gradient coating in Comparative Example 3;
[0033] Figure 7 This is a comparison chart of high temperature corrosion resistance of Examples 2-3, Comparative Examples 1-3, and Inconel625 and 12Cr1MoV. DETAILED DESCRIPTION
[0034] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0035] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0036] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0037] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0038] In the following embodiments, the aluminum alloy powder used is 2024 aluminum alloy powder with a particle size of 15-53 μm, and the particle sizes of Fe, Cr, and Al metal powders are also 15-53 μm; the matrix material used is 12Cr1MoV heat-resistant steel;
[0039] Example 1
[0040] This embodiment provides a method for preparing a laser cladding Al / FeCrAl gradient coating, which comprises the following steps:
[0041] (1) The surface of 12Cr1MoV heat-resistant steel is sandblasted to remove oxides, and then washed with anhydrous ethanol and dried for later use;
[0042] (2) Aluminum alloy coating was prepared on the surface of 12Cr1MoV heat-resistant steel by laser cladding process using 2024 aluminum alloy powder, wherein the processing parameters of laser cladding were: laser power 1250 W, scanning speed 50 mm / s, powder feeding speed 9 g / min, spot diameter 3 mm, and overlap rate 50%;
[0043] (3) Fe, Cr, and Al metal powders were mixed by ball milling at a mass percentage of 80%, 13%, and 7%, with a ball milling speed of 200 r / min, a ball milling time of 2 h, and a ball-to-material ratio of 10:1 to obtain FeCrAl metal mixed powder;
[0044] (4) FeCrAl alloy mixed coating was prepared on the aluminum alloy coating by laser cladding process using FeCrAl metal mixed powder, wherein the processing parameters of laser cladding were: laser power 2250 W, scanning speed 22 mm / s, powder feeding speed 12 g / min, spot diameter 3 mm, and overlap rate 50%.
[0045] Example 2
[0046] This embodiment provides a method for preparing a laser cladding Al / FeCrAl gradient coating, which comprises the following steps:
[0047] (1) The surface of 12Cr1MoV heat-resistant steel is sandblasted to remove oxides, and then washed with anhydrous ethanol and dried for later use;
[0048] (2) Aluminum alloy coating was prepared on the surface of 12Cr1MoV heat-resistant steel by laser cladding process using 2024 aluminum alloy powder, wherein the processing parameters of laser cladding were: laser power 1250 W, scanning speed 55 mm / s, powder feeding speed 9 g / min, spot diameter 3 mm, and overlap rate 50%;
[0049] (3) Fe, Cr, and Al metal powders were mixed by ball milling at a mass percentage of 80%, 13%, and 7%, with a ball milling speed of 200 r / min, a ball milling time of 2 h, and a ball-to-material ratio of 10:1 to obtain FeCrAl metal mixed powder;
[0050] (4) FeCrAl alloy mixed coating was prepared on the aluminum alloy coating by laser cladding process using FeCrAl metal mixed powder, wherein the processing parameters of laser cladding were: laser power 2250 W, scanning speed 22 mm / s, powder feeding speed 12 g / min, spot diameter 3 mm, and overlap rate 50%.
[0051] The present application conducts a performance test on the Al / FeCrAl gradient coating prepared in this embodiment, specifically: Figure 1 As shown in the figure, it can be seen that the Al / FeCrAl gradient coating has no obvious cracks, the coating is composed of columnar grains, and the thickness of the Al / FeCrAl gradient coating is about 800μm; in this embodiment, at the scanning speed when preparing the aluminum alloy coating, the thickness of the aluminum alloy coating formed on the surface of the 12Cr1MoV heat-resistant steel is about 250μm, and then the FeCrAl mixed coating is prepared by laser cladding on the aluminum alloy coating of this thickness, and a dense Al / FeCrAl gradient coating can be prepared. At the same time, from the XRD pattern ( Figure 3 ) It can be seen that an Al2O3 protective film is formed on the surface of the Al / FeCrAl gradient coating, which makes the Al / FeCrAl gradient coating have excellent corrosion resistance, high temperature stability and durability; and no obvious brittle phase (FeAl) appears in the Al / FeCrAl gradient coating of this embodiment. At the same time, after a high temperature corrosion test, its mass loss rate for 168h is 1989g / m -2 .
[0052] Example 3
[0053] This embodiment provides a method for preparing a laser cladding Al / FeCrAl gradient coating, which comprises the following steps:
[0054] (1) The surface of 12Cr1MoV heat-resistant steel is sandblasted to remove oxides, and then washed with anhydrous ethanol and dried for later use;
[0055] (2) Aluminum alloy coating was prepared on the surface of 12Cr1MoV heat-resistant steel by laser cladding process using 2024 aluminum alloy powder, wherein the processing parameters of laser cladding were: laser power 1250 W, scanning speed 66 mm / s, powder feeding speed 9 g / min, spot diameter 3 mm, and overlap rate 50%;
[0056] (3) Fe, Cr, and Al metal powders were mixed by ball milling at a mass percentage of 80%, 13%, and 7%, with a ball milling speed of 200 r / min, a ball milling time of 2 h, and a ball-to-material ratio of 10:1 to obtain FeCrAl metal mixed powder;
[0057] (4) FeCrAl alloy mixed coating was prepared on the aluminum alloy coating by laser cladding process using FeCrAl metal mixed powder, wherein the processing parameters of laser cladding were: laser power 2250 W, scanning speed 22 mm / s, powder feeding speed 12 g / min, spot diameter 3 mm, and overlap rate 50%.
[0058] The present application conducts a performance test on the Al / FeCrAl gradient coating prepared in this embodiment, specifically: Figure 2 As shown in the figure, it can be seen that the Al / FeCrAl gradient coating has no obvious cracks and other defects, and the overall thickness does not change much. This is because during the laser cladding process, Al atoms exist in the Al / FeCrAl gradient coating in the form of solid solution atoms. At the same time, compared with Example 2, due to the increase in the scanning speed when preparing the aluminum alloy coating, the thickness of the aluminum alloy coating formed on the surface of the 12Cr1MoV heat-resistant steel is 200μm, and then the FeCrAl mixed coating is prepared by laser cladding on the surface of the aluminum alloy coating of this thickness, and a dense Al / FeCrAl gradient coating can be prepared, as shown in FIG. Figure 3 As shown, no Al2O3 protective film can be formed on the surface of the Al / FeCrAl gradient coating, but no obvious brittle phase (FeAl) appears, which makes the Al / FeCrAl gradient coating have excellent corrosion resistance, high temperature stability and durability. That is, relative to Example 2, the Al / FeCrAl gradient coating in this embodiment has slightly lower comprehensive performance than the Al / FeCrAl gradient coating in Example 2.
[0059] Comparative Example 1
[0060] The present embodiment provides a preparation method of a laser cladding Al / FeCrAl gradient coating, and the preparation method is basically the same as that of Example 2, except that in the process parameters of the laser cladding of the aluminum alloy coating in step 2), the scanning speed is 22 mm / s, specifically: an aluminum alloy coating is prepared on the surface of 12Cr1MoV heat-resistant steel by a laser cladding process using 2024 aluminum alloy powder, wherein the processing parameters of the laser cladding are: laser power 1250 W, scanning speed 22 mm / s, powder feeding speed 9 g / min, spot diameter 3 mm, and overlap rate 50%.
[0061] The present application conducts a performance test on the Al / FeCrAl gradient coating prepared in the comparative example, specifically: In this embodiment, the macroscopic structure diagram of the Al / FeCrAl gradient coating prepared is as follows: Figure 4 As shown in the figure, it can be seen that the scanning speed when preparing the aluminum alloy coating is 22mm / s, and the thickness of the aluminum alloy coating formed on the surface of 12Cr1MoV heat-resistant steel is about 550μm. Then, the FeCrAl mixed coating is prepared by laser cladding on the surface of the aluminum alloy coating of this thickness. The FeCrAl mixed coating falls off, and the Al / FeCrAl gradient coating fails to completely cover the substrate material to form protection. This may be due to the slow scanning speed when preparing the aluminum alloy coating, resulting in a large thickness of the formed aluminum alloy coating, that is, there is a large amount of Al on the surface of the substrate material, and Al has low absorption efficiency for laser, which leads to the shedding of the FeCrAl mixed coating when preparing it on its surface, and fails to completely cover the substrate material to form protection.
[0062] Comparative Example 2
[0063] The present embodiment provides a preparation method of a laser cladding Al / FeCrAl gradient coating, and the preparation method is basically the same as that of Example 2, except that in the process parameters of the laser cladding of the aluminum alloy coating in step 2), the scanning speed is 33 mm / s, specifically: an aluminum alloy coating is prepared on the surface of 12Cr1MoV heat-resistant steel by a laser cladding process using 2024 aluminum alloy powder, wherein the processing parameters of the laser cladding are: laser power 1250 W, scanning speed 33 mm / s, powder feeding speed 9 g / min, spot diameter 3 mm, and overlap rate 50%.
[0064] The present application conducts a performance test on the Al / FeCrAl gradient coating prepared in the comparative example, specifically: In this embodiment, the macroscopic structure diagram of the Al / FeCrAl gradient coating prepared is as follows: Figure 5As shown in the figure, it can be seen that the scanning speed when preparing the aluminum alloy coating is 33mm / s, and the thickness of the aluminum alloy coating formed on the surface of the 12Cr1MoV heat-resistant steel is about 460μm. Then, the FeCrAl mixed coating is prepared by laser cladding on the surface of the aluminum alloy coating of this thickness. Figure 3 As shown in the figure, although an Al2O3 protective film is formed on the surface of the Al / FeCrAl gradient coating, a large amount of brittle phases (intermetallic compounds such as FeAl) are precipitated in the final Al / FeCrAl gradient coating. Al, as a solid solution strengthening element, improves the hardness of the Al / FeCrAl gradient coating while reducing its ductility and toughness, which leads to a large number of cracks in the Al / FeCrAl gradient coating and makes it impossible to obtain a dense composite coating.
[0065] Comparative Example 3
[0066] The present embodiment provides a method for preparing a laser-clad Al / FeCrAl gradient coating, and the preparation method is basically the same as that of Example 2, except that in the process parameters of the laser cladding of the aluminum alloy coating in step 2), the scanning speed is 44 mm / s, specifically: an aluminum alloy coating is prepared on the surface of 12Cr1MoV heat-resistant steel by a laser cladding process using 2024 aluminum alloy powder, wherein the processing parameters of the laser cladding are: laser power 1250 W, scanning speed 44 mm / s, powder feeding speed 9 g / min, spot diameter 3 mm, and overlap rate 50%.
[0067] The present application conducts a performance test on the Al / FeCrAl gradient coating prepared in the comparative example, specifically: In this embodiment, the macroscopic structure diagram of the Al / FeCrAl gradient coating prepared is as follows: Figure 6 As shown in the figure, it can be seen that the scanning speed when preparing the aluminum alloy coating is 44mm / s, and the thickness of the aluminum alloy coating formed on the surface of 12Cr1MoV heat-resistant steel is about 300μm. On the surface of the aluminum alloy coating with this thickness, the FeCrAl mixed coating is prepared by laser cladding, as shown in FIG. Figure 3 As shown in the figure, although an Al2O3 protective film is formed on the surface of the Al / FeCrAl gradient coating, the content of brittle phase (intermetallic compounds such as FeAl) precipitated in the final Al / FeCrAl gradient coating is reduced (relative to Comparative Example 2), and Al, as a solid solution strengthening element, improves the hardness of the Al / FeCrAl gradient coating while reducing its ductility and toughness, thereby causing cracks to penetrate the coating in the Al / FeCrAl gradient coating, but the number of such cracks is reduced compared to Comparative Example 2.
[0068] Comparative Example 4
[0069] The present embodiment provides a method for preparing a laser cladding FeCrAl coating, and the preparation method is basically the same as that of Example 2, except that the FeCrAl alloy mixed coating is directly prepared on the surface of the base material by laser cladding technology, and the mass proportion of each element of Fe, Cr and Al in the FeCrAl alloy mixed coating is the same as that of the Al / FeCrAl gradient coating in Example 2.
[0070] Specifically:
[0071] (1) The surface of 12Cr1MoV heat-resistant steel is sandblasted to remove oxides, and then washed with anhydrous ethanol and dried for later use;
[0072] (2) taking Fe, Cr and Al metal powders according to mass percentage and mixing them by ball milling, the ball milling speed is 200 r / min, the ball milling time is 2 h, and the ball-to-material ratio is 10:1, to obtain FeCrAl metal mixed powder;
[0073] (3) FeCrAl alloy mixed coating was prepared on the aluminum alloy coating by laser cladding process using FeCrAl metal mixed powder, wherein the processing parameters of laser cladding were: laser power 2250 W, scanning speed 55 mm / s, powder feeding speed 12 g / min, spot diameter 3 mm, and overlap rate 50%.
[0074] The FeCrAl coating prepared in this embodiment has a thickness equivalent to that of the Al / FeCrAl gradient coating in Example 2, and its mass loss rate at 168h is 2143 g / m -2 , the high temperature corrosion resistance is not as good as that of the Al / FeCrAl alloy mixed coating in Example 2. This shows that without changing the coating thickness, the preparation of Al / FeCrAl gradient coating can effectively improve the high temperature corrosion resistance of the coating.
[0075] The present application also conducts high temperature corrosion resistance tests on Inconel 625, the coatings prepared in Examples 2-3, and Comparative Examples 1-3, and the base material 12Cr1MoV, specifically:
[0076] Test method: Cut the coating into samples of 17mm*17mm*5mm, seal the five sides of the sample with castable alumina material, leaving the coating surface, sprinkle 5g of mixed salt of NaCl:KCl:Na2SO4:K2SO4=1:1:4:4 on the surface of the sample, place it in a high-temperature box furnace at 650℃, measure its weight loss every 24h to evaluate its high-temperature corrosion resistance.
[0077] The results are as follows Figure 7 As shown, from Figure 7 It can be seen that Example 2 has the best high temperature corrosion resistance, and its 168h mass loss rate is 1989g / m-2 The mass loss rate of the commercially available nickel-based alloy Inconel 625 after 168 hours is 1925 g / m -2 The 168h mass loss rate of the commonly used boiler heat-resistant steel 12Cr1MoV is 4083g / m -2 In summary, the high temperature corrosion resistance of the Al / FeCrAl gradient coating in Example 2 has reached 97% of that of the Inconel 625 alloy, which is 2 times higher than that of the substrate, but the cost is about 20% of that of the Inconel 625 alloy. Therefore, the present invention has excellent high temperature corrosion resistance while reducing the cost, and can further expand the application of laser cladding coatings in the field of waste incineration power generation.
[0078] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A laser cladding Al / FeCrAl gradient coating for waste incineration conditions, characterized in that: The invention comprises an aluminum alloy coating arranged on the surface of a base material, and a FeCrAl alloy mixed coating arranged on the surface of the aluminum alloy coating.
2. The laser cladding Al / FeCrAl gradient coating according to claim 1, characterized in that: The thickness of the laser cladding Al / FeCrAl gradient coating is 0.5-1.2 mm.
3. The laser cladding Al / FeCrAl gradient coating according to claim 1 or 2, characterized in that: The particle size of the aluminum alloy powder in the aluminum alloy coating is 15-53 μm, the particle size of the Fe, Cr, and Al metal powder in the mixed coating is 15-53 μm, and the mixed coating includes Fe: 75-85%, Cr: 10-15%, and Al: 4-10% by mass percentage.
4. A method for preparing a laser cladding Al / FeCrAl gradient coating according to any one of claims 1 to 3, characterized in that: The steps include: 1) Pre-treat the substrate material by sandblasting to remove oxides, and clean it with anhydrous ethanol and then dry it; 2) Using laser cladding process to prepare aluminum alloy coating on the surface of substrate material; 3) In terms of mass percentage, metal powders of Fe: 75-85%, Cr: 10-15%, and Al: 4-10% are mixed, and a uniform powder is obtained by vacuum ball milling. Subsequently, a FeCrAl alloy mixed coating is prepared on the surface of the aluminum alloy coating by a laser cladding process.
5. The method for preparing the laser cladding Al / FeCrAl gradient coating according to claim 4, characterized in that: The method further includes, before step 1), sandblasting or mechanically grinding the surface of the base material to remove oxides.
6. The method for preparing the laser cladding Al / FeCrAl gradient coating according to claim 4, characterized in that: In step 2), the processing parameters of the laser cladding are: laser power is 1000-1500 W, scanning speed is 50-66 mm / s, powder feeding speed is 6-12 g / min, and spot diameter is 3 mm.
7. The method for preparing the laser cladding Al / FeCrAl gradient coating according to claim 4, characterized in that: In step 3), the processing parameters of the laser cladding are: laser power 1500-2500 W, scanning speed 11-44 mm / s, powder feeding speed 9-15 g / min, and spot diameter 3 mm.
8. The method for preparing a laser cladding Al / FeCrAl gradient coating according to claim 4, characterized in that: In step 3), the ball milling conditions are as follows: a rotation speed of 100-200 r / min, a ball-to-material ratio of 8:1-12:1, and a ball milling time of 2-6 h.
9. The method for preparing a laser cladding Al / FeCrAl gradient coating according to claim 4, characterized in that: The particle sizes of the aluminum alloy powder, and the Fe, Cr, and Al metal powders are all 15-53 μm.
10. A laser cladding Al / FeCrAl gradient coating according to any one of claims 1 to 3 suitable for high temperature sulfate and chloride corrosion in a waste incineration power generation environment.